Non-durational acoustic correlates of word-initial consonant gemination in Kelantan Malay: The potential roles of amplitude and f0. (2nd April 2020) - Hamzah, Mohd Hilmi; Hajek, John; Fletcher, Janet
Abstract : This study reports on non-durational acoustic correlates of typologically rare word-initial consonant gemination in Kelantan Malay (KM) by focusing on two acoustic parameters – amplitude and f0. Given the unusual characteristics of the word-initial consonant contrast and its potential maintenance in domain-initial environments, this study sets to examine the extent to which amplitude and f0 can potentially characterise such a contrast in KM in addition to the cross-linguistically established acoustic correlate of closure duration. The production data involved elicited materials from sixteen KM native speakers. RMS and f0 values were measured at the start of the vowel following stops and sonorants produced in isolation (i.e. utterance-initial position) and in a carrier sentence (i.e. utterance-medial position). Results indicate that the consonant contrast is reflected in systematic differences in (i) vowel onset amplitude and f0 following the target consonant and (ii) the ratios of amplitude and f0 across two syllables of disyllabic words. There are also effects of utterance position, manner of articulation and voicing type on the magnitude of contrast between singletons and geminates with utterance-initial voiceless stops generally showing the greatest magnitude difference. The conclusion is drawn that the KM word-initial singleton/geminate consonant contrast can be associated with a set of acoustic parameters alongside closure duration.